2011
DOI: 10.1111/j.1442-1984.2011.00314.x
|View full text |Cite
|
Sign up to set email alerts
|

Germination and emergence of Ambrosia artemisiifolia L. under changing environmental conditions in China

Abstract: Laboratory and greenhouse studies were conducted to determine the effects of key environmental factors on germination and seedling emergence of the invasive weed Ambrosia artemisiifolia L. (common ragweed) collected from Mudanjiang (temperate climate), Nanjing (temperate-subtropical) and Nanchang (subtropical) in China. Germination of seeds occurred at temperatures ranging from 5 to 40°C, under both a 12-h photoperiod and continuous darkness. Germination success exceeded 48% in solutions with pH values between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 23 publications
4
24
0
Order By: Relevance
“…It was shown in Banksia woodlands in south-western Australia by Pérez-Fernández et al (2000) as well as by Young et al (2015) for perennial grasslands in north-central California. These results were obtained for Ambrosia artemisiifolia L. (Sang. et al 2011), Malva pusilla Sm.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…It was shown in Banksia woodlands in south-western Australia by Pérez-Fernández et al (2000) as well as by Young et al (2015) for perennial grasslands in north-central California. These results were obtained for Ambrosia artemisiifolia L. (Sang. et al 2011), Malva pusilla Sm.…”
Section: Discussionmentioning
confidence: 55%
“…Usually, invasive species have wide range of temperatures under which they germinate. Such data were obtained for Ambrosia artemisiifolia which corresponds with the wide distribution of the species in China (Sang et al 2011), and is again reflected by other successful invasive weeds, such as Cortaderia jubata (Lem.) Stapf (8-35°C) (Drewitz & DiTomaso 2004), Solanum viarum Dunal (10-35°C) (Akanda et al 1996) and Pueraria lobata (Willd.)…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…These ecophysiological adaptive traits in A. artemisiifolia have likely contributed to the the successful invasion and range expansion of this species in many parts of temperate Europe (Fumanal et al 2008), and also in subtropical regions such as observed recently in southern China Qi et al 2011). This better understanding of how acclimation to irradiance in A. artemisiifolia may affect its colonizing and invasive success will facilitate the prediction of future invasions and range transformations in relation to the projected climate change and general evolutionary potential of invasive plants (Clements and DiTommaso 2011;Sang et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The species continue their southward spread into the subtropical regions of the country (Qin et al, 2012). The reason of the large-scale invasion of A. artemisiifolia in China is its great germination success over the highly variable climatic conditions (Sang et al, 2011). Li et al (2012) found that high levels of genetic variation in China indicate that there has been no erosion of genetic variance due to a bottleneck during the introduction process.…”
Section: Ragweed In Individual Countries Worldwidementioning
confidence: 99%